ACHIEVING PAKIS’S THERMAL CONDUCTIVITY AS ARCHITECTURAL BUILDING THERMAL RESISTANT BY GUARDED STEADY-STATE HOTBOX METHOD:PART 1 - Danny Santoso Mintorogo; Mohd. Hamdan Ahmad (Dimensi: Journal of Architecture and Built Environment, 2011)
Thermal conductivity of various materials which are mostly listed available as building or industrial materials in reference books and websites; but one will hardly find out for every new material, and has to be observed and try out itself if we want to know the new thermal conductivity value (k). Nonetheless with new substanct likes pakis-stem blocks that come from natural tree that could be found in the tropical woodland of Indonesia. Steady-state homogeneous temperature applied with hotbox method in an uninfluent environment likes guarded laboratory environment is the right method to obtain the thermal conductivity and resistance of porousness and semi-solidness of the pakis-stem blocks. After investigating almost 24 hours with controller TRSYS01 applying with ASTM C1155, physical semi-solid pakis blocks tend to be more easy to obtain the R-value, k-value, and surface temperatures than the porous pakis. The porous pakis blocks were tend to unstable during the test due to its physical permeable condition. The resistant values (R-value) and thermal conductivity (k) values will be further published on the following discussion of pakis thermal conductivity part 2.